Enhancing visualizations in pedagogical debuggers by leveraging on code analysis - André L. Santos (18th Koli Calling International Conference on Computing Education Research, 2018)
PandionJ is a pedagogical debugger that provides users with rich visualizations of program state that resemble teacher-drawn illustrations. Its design was driven by a study that investigated how programming teachers illustrate variables, transposing illustration patterns into the tool. These illustrations require static analysis of the source code to infer relationships between variables. We describe the innovative features of the tool regarding how it addresses program variables. The tool was adopted in an introductory programming course, and the pass rates of the first course edition using it were significantly higher when compared to the three previous editions.